2013
DOI: 10.5657/fas.2013.0093
|View full text |Cite
|
Sign up to set email alerts
|

The First Report of a Megalocytivirus Infection in Farmed Starry Flounder, Platichthys stellatus, in Korea

Abstract: In 2009, a systemic megalocytivirus infection associated with high mortality was detected for the first time in cultured starry flounder Platichthys stellatus in Korea. Diseased starry flounder had pale bodies and gill coloring and enlarged spleens. Histopathological examinations revealed basophilic enlarged cells in various organs of diseased starry flounder. Polymerase chain reaction (PCR) was performed on tissue samples using three published primer sets developed for the red sea bream iridovirus. PCR produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
1
10
1
1
Order By: Relevance
“…For this reason, attention has been paid to efforts to increase the capacity of the farming practices for this candidate species. Megalocytivirus infection in starry flounder was first reported in Korea and classified as megalocytivirus type 3 with the high homology of MCP gene with those of FLIV and TRBIV by Won et al (). However, it remains unclear whether megalocytivirus type 3 from starry flounder can cause mortality in fish species other than targeted fishes or whether subclinical infection with megalocytiviruses occurs.…”
mentioning
confidence: 99%
“…For this reason, attention has been paid to efforts to increase the capacity of the farming practices for this candidate species. Megalocytivirus infection in starry flounder was first reported in Korea and classified as megalocytivirus type 3 with the high homology of MCP gene with those of FLIV and TRBIV by Won et al (). However, it remains unclear whether megalocytivirus type 3 from starry flounder can cause mortality in fish species other than targeted fishes or whether subclinical infection with megalocytiviruses occurs.…”
mentioning
confidence: 99%
“…Recently, megalocytiviruses have been divided into three genotypes (RSIV, ISKNV and TRBIV) based on their MCP gene sequences [ 6 ]. Due to the traditional knowledge about the geographic restriction and the narrow host range, iridovirus epizootics resulting from TRBIV-like megalocytiviruses have been so far rare to be discovered in the global areas except East Asia [ 6 , 12 , 13 , 14 , 22 , 23 ]. Thus, TRBIV-like megalocytiviruses are not included in the OIE-reportable virus list [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both RSIV- and ISKNV-induced iridoviral diseases are listed by the World Organization for Animal Health (OIE) as notifiable diseases in fish [ 6 ]. However, in contrast to RSIV- and ISKNV-like viruses, TRBIV-like megalocytiviruses are traditionally restricted to China [ 12 , 22 ] and South Korea [ 13 , 14 , 23 ] around the Yellow Sea in East Asia and mainly affect flatfishes, such as flounder and turbot [ 6 ]. Further genetic sequence investigations of more megalocytivirus isolates revealed that each genotype (RSIV, ISKNV and TRBIV) of the genus Megalocytivirus can be subdivided into two separate clades [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Megalocytiviruses have been studied extensively due to their ability to cause significant diseases in a wide range of cultured freshwater and marine species (Kurita & Nakajima, ; Subramaniam et al., ). Studies have shown that megalocytiviruses infect more than hundreds of species of aquatic vertebrates including fish, amphibians and reptiles and cause high mortality and problems with wildlife conservation (Rimmer et al., ; Williams, Barbosa‐Solomieu, & Chinchar, ; Won et al., ). Infectious spleen and kidney necrosis virus (ISKNV) causes hypertrophy of the infected cells, causing them to become much larger than healthy cells (He, Zeng, Weng, & Chan, ).…”
Section: Introductionmentioning
confidence: 99%